History of Transportation in Central Asia - Saidbahrom, Saidusmonov (Research Parks Publishers, 2023)
The importance of transport in the development and placement of production forces is incomparable. Transport is an important basis of production infrastructure in any region. An area of any scale cannot be developed effectively and rationally without transport. The article discusses the history and prospects of the development of transport in Central Asia.